Development of Ketchup from Sudanese Red karkade (Hibiscus sabdariffa L.) byproduct - Abdel-Rahman, Nawal Abdel-Gayoum (Food Biology)
The aim of this study is to use of karkede (Hibiscus sabdariffa L.) byproduct as raw material to make ketchup instead of tomato. Ketchup is making of various pulps, but the best type made from tomatoes. Roselle having adequate amounts of macro and micro elements, and it is rich in source of anthocyanine. The ketchup made from pulped of waste of soaked karkede, and homogenized with starch, salt, sugar, ginger (Zingiber officinale), kusbara (Coriandrum sativum) and gum Arabic. Then processed and filled in glass bottles and stored at two different temperatures, ambient and refrigeration. The total solids, total soluble solids, pH, ash, total titratable acidity and vitamin C of ketchup were determined. As well as, total sugars, reducing sugars, colour density, and sodium chloride percentage were evaluated. The sensory quality of developed product was determined immediately and after processing, which included colour, taste, odour, consistency and overall acceptability. The suitability during storage included microbial growth, physico-chemical properties and sensory quality. The karkede ketchup was found free of contaminants throughout storage period at both storage temperatures. Physico-chemical properties were found to be significantly differences at p?0.05 level during storage. There were no differences between karkade ketchup and market tomato ketchup concerning odour, taste, odour, consistency and overall acceptability. These results are encouraging for use of roselle cycle as a raw material to make acceptable karkade ketchup.